The Influence of Transformational Leadership Styles to Performance with Knowledge Sharing Behavior Mediation at the Bawaslu of Jepara Regency - Mahfudh, Ainul; Arba'ani, Muhammad Anas; Riyoko, Sisno; Arifin, Samsul (Universitas Pamulang, 2024)
This study looked at how the Jepara Regency Bawaslu's culture of information sharing affected employee performance in relation to transformational leadership style. The 361 Bawaslu employees in Jepara Regency that made up the population used in this study were divided into 20 Bawaslu employees in Jepara, 156 Panwascam employees, and 185 village/sub-district election supervisory committee members. The sample size was calculated using the Slovin formula, and 163 persons made up the study's sample. The data were assessed using structural equation modeling with partial least squares (SEM-PLS). and determine how connected the independent and dependent variables were in the research. Multiple linear analyses were employed in Data analysis for testing hypotheses in this study as well as validity and reliability assessments of the questionnaire. The study's conclusions showed that transformational leadership had no effect on the performance of Jepara Bawaslu personnel. The study's findings provide more evidence of the positive effects transformational leadership has on cultures that value information sharing. Knowledge-sharing cultures have a favorable and substantial effect on performance. Additionally, transformational leadership has a considerable effect on employee performance when knowledge-sharing cultures are taken into account as an intervening variable.